Social Constructionism as a theoretical approach to understand sexual abuse - Magnabosco Marra, Marlene (Pontificia Universidad Católica del Perú, 2014)
The text aims to discuss Social Constructionism as a theoretical approach for understanding sexual abuse. This approach enables the construction of new narratives, and creates conditions for the reinterpretation of the situations lived due to sexual abuse. It will furthermore help the person construct a more positive story of his/her life and identity. While narrating stories of sexual abuse, families get to know and perceive other new narrative sequences, finding a meaning that corresponds to the lived moment. These special conversations invite the reconstruction of a new narrative and enable a more reflective and critical position about violence. Additionally, there is a modification in the relation between the people involved in the conversation.